Improvement of Transient Performance in Microgrids: Comprehensive Review on Approaches and Methods for Converter Control and Route of Grid Stability - Mandarapu Srikanth; Y. V. Pavan Kumar; Mohammad Amir; Sukumar Mishra; Atif Iqbal (IEEE Open Journal of the Industrial Electronics Society, 2023)
In conventional power systems, stability is ensured successfully because of large synchronous generators, where, during transient conditions, the inertia and dynamics of the synchronous generators help to retain stability. On the contrary, inverter-interfaced distributed energy resources suffer from maintaining stability because of their quick dynamics (opposite to the concept of inertia). Therefore, there exists a tradeoff between response and stability aspects and this is referred to as transient performance problem in microgrids. Conventionally, this problem is addressed from the controller side by increasing its bandwidth thereby leading to better disturbance rejection and immunity against parameter changes. Since the classification of the disturbances (as small or large) is not straightforward and uncertain, an increase in the controller's bandwidth beyond a certain limit is not possible. Therefore, it is understood that the transient performance improvement cannot be achieved from the controller alone. Hence, the chances of improving performance from other approaches in the case of grid-connected mode and advanced control strategies for the controller in the case of islanded mode need to be investigated. With this intent, a comprehensive investigation of state-of-the-art approaches and methods to improve transient performance in microgrids is carried out in this article. This work is carried out in three stages. Initially, it explores various technical challenges that are involved and possible approaches to address these challenges. Next, a critical review of each approach is carried out based on their philosophy to improve transient performance. Furthermore, a comparative analysis that projects the scope of each approach is elucidated. Finally, some future research directions are proposed to enhance the effectiveness of key approaches.